Educação estética e a poética do oprimido: um relato sobre a experiência construída durante as aulas de teatro educação com alunos do ensino médio - Araújo, Francisco Wesley de (2024)
The research arose from concerns as an Art teacher, serving high school students in basic education, while observing the persistence of banking education in the Brazilian educational context. Inspired by Paulo Freire (2023) and Augusto Boal (2009), the driving question of the research was to understand and experiment with a more critical and aesthetically centered teaching approach in order to overcome the disconnection between school content and students' reality. Objectively, the proposal sought to integrate techniques from Boal's Poetics of the Oppressed (2009) as a pedagogical approach in elective theater classes, aiming for significant transformations in the perception of those involved in the researched context regarding the construction of an aesthetic thought about Art and Education.Considering the researcher's immersion in the field as a teacher, data production, and analysis were based on the cartographic method (Kastrup, 2015), as intervention research, while also approaching Art Based Education Research (ABER) by placing my own practice as an artist-teacher at the center of the investigation. The logbook was adopted as a privileged instrument for recording the collective experiences of the participants, which was observed from the perspective of the teacher- researcher. Thus, the following text reports aspects of the pedagogical work carried out with the students, which initially sought to investigate how the Poetics of the Oppressed could stimulate symbolic and sensitive thinking but emphasized the need to transform Theater Education classes into meaningful environments. Breaking with the static narrative of banking education, while contextualizing, it narrates a unique research experience, which contributes to thinking about the integral formation of students and reflecting on the practice of the artist- researcher-teacher. Finally, the analysis of the data collected during the research points to the importance of the experience with art in the process of the students' aesthetic education and to the need to bring teachers and students closer together in search of more contextualized content with reality, thus establishing a dialogical and humanistic education.